571 ANV419 is a novel CD122-selective IL-2/anti-IL-2 antibody fusion protein with potent CD8 T cell and NK cell stimulatory function in vitro and in vivo. (10th December 2020) - Huber, Christoph; Katopodis, Andreas; Branetti, Barbara; Rondeau, Jean-Michel; Popp, Simone; Regnier, Catherine; Kaiser, Daniel
Abstract : Background: ANV419 is a uniquely engineered IL-2 fusion to an antibody selectively blocking the IL-2 receptor alpha (CD25) binding site. It signals selectively through the CD122/CD132 dimeric IL-2 receptor and stimulates the proliferation of CD8 T cells and NK cells while avoiding the proliferation of immunosuppressive regulatory T cells (Treg). Therefore, ANV419 has the potential to substantially separate targeted T-cell and NK cell proliferation and anti-tumor responses from the dose limiting toxicities of recombinant IL-2 (aldesleukin). ANV419 has antibody like stability and behavior and is currently in late preclinical development for tumor immunotherapy. Methods: The crystal structure of ANV419 has been solved and its binding affinity to CD25 and CD122 has been determined. In vitro and in vivo studies, including pharmacodynamics and toxicity, have been performed in rodents and non-human primates. The ability of ANV419 to inhibit tumor growth has been studied in mouse syngeneic models. Results: Structural analysis demonstrates that the CD25 binding site of IL-2 is completely blocked in ANV419 while the CD122/CD132 sites are available for binding. As a result, ANV419 lacks CD25 binding activity but retains IL-2 receptor beta (CD122) affinity comparable to native IL-2. In human peripheral blood monocyte cultures, ANV419 induces STAT5 phosphorylation with high selectivity for CD8 and NK cells but not Treg. Concordantly, it stimulates the proliferation of purified human CD8 T cells and NK cells but not CTLL-2 cells. A single injection of ANV419 in mice results in strong induction of the proliferation marker Ki67 specifically in CD8 T cells and NK cells but not Tregs and a selective increase of the respective cell numbers in the spleen and peripheral blood of animals. Single agent anti-tumor activity was observed in checkpoint sensitive (H22) and resistant (Renca, B16F10) syngeneic mouse tumor models. Combination of ANV419 with trastuzumab in the gastric cancer N87 xenograft model in BALB/c nude mice led to significant tumor reduction relative to trastuzumab monotherapy. In non-human primates, ANV419 is well tolerated and induces expression of Ki67 and sustained expansion in CD8 T cells and NK cells with no signs of vascular leak syndrome observed with high dose aldesleukin in patients. Conclusions: The pre-clinical data suggest that ANV419 possesses a unique structure and is potent in expanding CD8 T-cells and NK cells with a marked safety window in non-human primates. This data warrants further translational development of ANV419 as an immune therapeutic in oncology.